2015
DOI: 10.1177/1535370215611972
|View full text |Cite
|
Sign up to set email alerts
|

Influence of doxazosin on biosynthesis of S100A6 and atrial natriuretic factor peptides in the heart of spontaneously hypertensive rats

Abstract: Hypertension frequently results in severe complications in cardiovascular system and histopathological changes in the heart. To better understand the cellular processes and signaling pathways responsible for the proper functioning of the heart, we decided to check whether doxazosin affects the density of structures containing S100A6 and atrial natriuretic factor in the heart of spontaneously hypertensive rats. The aim of this study is to find differences in the density of the structures containing S100A6 and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…There are many reports showing that S100A6 level increases under stress conditions such as ischemia [ 123 ], mechanical force [ 124 ], irradiation [ 24 ], oxidative stress [ 125 ], hypertension [ 126 ] or kainic acid treatment [ 127 ]. All these conditions may lead to cell apoptosis and inflammation followed, depending on the extent of tissue damage, by regeneration [ 128 ].…”
Section: Structural Aspects Of S100a6—ligand Interactionsmentioning
confidence: 99%
“…There are many reports showing that S100A6 level increases under stress conditions such as ischemia [ 123 ], mechanical force [ 124 ], irradiation [ 24 ], oxidative stress [ 125 ], hypertension [ 126 ] or kainic acid treatment [ 127 ]. All these conditions may lead to cell apoptosis and inflammation followed, depending on the extent of tissue damage, by regeneration [ 128 ].…”
Section: Structural Aspects Of S100a6—ligand Interactionsmentioning
confidence: 99%
“…CASP1 [185], FOXP3 [186], SOCS1 [187], GATA6 [188], IRF7 [189], POSTN (periostin) [190], CYP19A1 [191], CD36 [192], LYN (LYN proto-oncogene, Src family tyrosine kinase) [193], CD4 [194], LEPR (leptin receptor) [195], AR (androgen receptor) [196], FOXO1 [197] and PON2 [198] are a potential biomarkers for the detection and prognosis of PCOS. Udjus et al [199] Benjafield et al [200], Shetty et al [58], Kassan et al [201], Wetzl et al [202], Le Hiress et al [203], Pal-Ghosh et al [204], Niu, [205], Fan et al [206], Deng et al [207], Chen et al [208], Sardo et al [209], Seidel et al [210], Zhu et al [211], Omura et al [212], Hu et al [213], Castoldi et al [214], Yoshida et al [215], Palao et al [216], Kušíková et al [217], Decharatchakul et al [218], Ahmed et al [219], Merklinger et al [220], Lei et al [146], Liu et al [221], Chen et al [222], Tan et al [223], Shi et al [224], Ikonnikova et al [225], Shimodaira et al [226], Pravenec et al [227], Zhang et al [228], Shah et al [229], Cicekliyurt and Dermenci [230], Ong et al [98], Nowzari et al [163], Kim et al [231], Bonafiglia et al [232], Selle et al [233],Yoo et al [234], Kasacka et al [235], Wang et al [236], Huang et al [237], Caceres et al [238], Lei et al [239], Lu et al [240], Cui et al [241], Xiao et al [242], Hiramatsu et al [243], Oliver et al [244], Grabowski et al [245], Zhu et al [246] and Li et al [247] demonstrated that the altered expression of CASP1, EDNRA (endothelin receptor type A), F2RL1, FOXP3, TIMP4, CD74, PLK1, TGFB1, GATA6, IRF7, IRF9, BGN (biglycan), C...…”
Section: Discussionmentioning
confidence: 99%
“…S100A6 is a member of the S100 protein family ( 15 ). S100A6 has a number of biological functions, including participating in the degradation and ubiquitination of β-catenin, promoting apoptosis, interacting with extracellular matrix proteins, enhancing cell metabolism and skeleton depolymerization, participating in endocytosis and exocytosis, adjusting enzyme activity, inhibiting protein kinase C-mediated phosphorylation and participating in gene transcription ( 16 , 17 ). A number of studies have demonstrated that S100A6 is also associated with the occurrence and development of tumors and is upregulated in several tumors, including ovarian cancer, colorectal cancer, pancreatic cancer, liver cancer, malignant melanoma and osteosarcoma ( 18 , 19 ).…”
Section: Discussionmentioning
confidence: 99%